A Pilot Study Considering Ecoroofs as Therapeutic Landscapes - Starry, Olyssa; Viray, Arjun; Park-Egan, Brenna; Terway, Amber Collett; Oxendahl, Timothy; Burdsall, Tina (Frontiers in Sustainable Cities, 2022)
The potential for urban open spaces to convey therapeutic benefits is increasingly substantiated. More work is needed to specifically consider how low impact designs to manage stormwater such as ecoroofs perform in this context. Here, we report on a pilot study addressing: 1) factors determining whether a hospital has an ecoroof, and 2) how ecoroofs might convey therapeutic benefits. We utilized a mixed methods approach which encompassed phone interviews of hospital ecoroof managers as well as analysis of national hospital databases. We also conducted a local case study which compared cortisol samples and stress indicators from patients, staff, and caregivers visiting an ecoroof to those waiting indoors at the Oregon Health and Sciences University in Portland OR. Behavioral observations took place at this same location. In 2017, we identified 105 hospitals with ecoroofs in the contiguous United States. Our analysis of a national hospital database found two factors that significantly increased the likelihood of a hospital having an ecoroof: Medicaid discharges per year; and non-profit status. Interviews with practitioners nationally revealed a wide range of motivations but that therapy was a consideration for a majority, but notably not all, of the hospitals surveyed. They similarly noted variation in roof design, maintenance, and programming around horticultural therapy; we highlight some best practices here. Our physiological case study was limited in sample size. Preliminary findings showed that salivary cortisol levels varied by ecoroof visitor type, ranging on average from 0.09µg/ml for caregivers to 0.30 µg/ml for patients. We did not observe any significant changes in visitor cortisol. This could be explained by low replication or the short treatment duration. Alternatively, these pilot data may indicate a gap in horticultural therapy theory vs practice. Behavioral observations demonstrated a wide array of different uses of the ecoroof space such as cell phone use and passing by. Though preliminary, our findings suggest that therapeutic effects may vary by user type and activity and depend on roof design and goals. This study offers both information on the therapeutic potential of hospital ecoroofs as well as lessons learned regarding different approaches to researching this somewhat new topic.